SISTEM INFORMASI NILAI SEKOLAH DASAR NEGERI II DOMAS - , ICHWAN NURHUDA, Mardhani Riasetiawan, SE., Ak., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Elementary School of II Domas is one of the educational institutions in the Wonogiri. Currently recording student data, teacher data, school data and student grade data are still using the manual method. Student data recorded using blank form and stored in the administration. How to manually takes a long time to search of data. Management student grade data consists of two stages. The teacher collects the results of students grade to the class guardian and the class guardian make grade reporting. The way it causes a delay in making the grade report. Based on these problems, is need to build a system that is able to handle the process of recording student data, teacher data, school data and students grade data and be able to handle the grade reporting. Grade Information Systems Elementary School of II Domas was built using laravel framework and MySQL database. The system can perform recording student data, teacher data, school data and value data, and preparing grade reports.